Kelayakan Finansial Penerapan Green Technology pada Pengelolaan Sampah Perkotaan: Indonesia - Sri Hutami Adiningsih S; Wulan Purnamasari (PT. Lontara Digitech Indonesia, 2025)
Population growth and increased economic activity in urban areas have led to an increase in waste volume that requires more effective, efficient, and environmentally friendly handling. Green technology is a modern alternative that can optimize waste processing processes while generating additional economic value through the use of energy, compost, and recycled materials. This study aims to analyze the financial feasibility of implementing green technology in urban waste management using Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (BCR), and Payback Period (PP) indicators. The research method used is a quantitative approach through a feasibility study with primary and secondary data obtained from observations, interviews, and waste management documents. The results show that the total initial investment is IDR 1,500,000,000 with an annual net benefit of IDR 350,000,000. Based on the analysis, a positive NPV value of IDR 460,000,000, an IRR of 13.8%, a BCR of 1.22, and a Payback Period of 4.3 years was obtained. These results indicate that the application of green technology in urban waste management is financially feasible. This study recommends that city governments consider implementing green technology in stages, increasing institutional capacity, and establishing partnerships with the private sector to optimize the effectiveness and sustainability of modern waste management systems.